Immunomodulatory Potential of Starfruit (Averrhoa bilimbi L.) Extract on Neutrophil-to-Lymphocyte Ratio (NLR) Values in Mice Induced by Salmonella enterica Serovar Typhimurium - Yessy Sabna Sari Manalu; Revis Asra; Fitra Wahyuni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Infectious illnesses continue to be a significant health issue around the globe, especially in underdeveloped nations like Indonesia. Salmonella is a type of bacteria that leads to widespread infections. According to the World Health Organization (WHO), there were 9 million instances of typhoid fever in 2019, causing about 110,000 fatalities each year. Starfruit (Averrhoa bilimbi L.) is a type of plant that has secondary metabolites capable of affecting the immune system. The purpose of this study was to determine the effect of starfruit (Averrhoa bilimbi L.) fruit extract on the Neutrophil-Lymphocyte Ratio (NLR) value in mice infected with Salmonella typhimurium bacteria. The method used in this study was a true experimental study with a Completely Randomized Design (CRD). The collected data were evaluated using the Statistical Package for the Social Sciences (SPSS) software, which included tests for homogeneity and normality, followed by additional analysis with the Duncan Multiple Range Test (DMRT). The findings of the research revealed that the extract from starfruit (Averrhoa bilimbi L.) consists of secondary metabolites, including alkaloids, flavonoids, tannins, saponins, and triterpenoids. These secondary metabolites serve as immunomodulators and may influence Neutrophil-lymphocyte Reactivity (NLR), as shown by a statistical analysis (p<0.05) in mice infected with Salmonella typhimurium at doses of 700mg per kg of body weight.